Surface treatment by oxidizing the plates can alter the response of protein crystallization. (4th February 2014) - Guo, Yun‐Zhu; Liu, Yong‐Ming; Yin, Da‐Chuan; He, Jin; Zhang, Chen‐Yan; Cao, Hui‐Ling; Hou, Hai; Ma, Wei; Guo, Wei‐Hong; Shi, Jian‐Yu; Cui, Chao; Wang, Zhe; et al.
<x xml:space="preserve">Abstract</x> This report describes the modification of crystallization plates by simply oxidizing the surface of the protein wells. The oxidized crystallization plates were tested in standard protein crystallization screening and reproducibility studies. The results showed that the protein wells of the treated plates were smoother and more optically transparent than those of the untreated plates, and more importantly, protein crystallization was significantly promoted after the oxidation treatment. Because there is no change to the routine screening protocol, this method is simple and easy to apply in protein crystallization.